2020
DOI: 10.3389/fevo.2020.00260
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Ecological Uniqueness of Andean Diatom Communities Are Correlated With Climate, Geodiversity and Long-Term Limnological Change

Abstract: Benito et al.Ecological Uniqueness of Andean Diatoms trends for the last ca. 200 years, indicating that biotic homogenization is not widespread across the tropical Andes. Our approach for unifying diatom ecology, metacommunity, and paleolimnology can facilitate the understanding of future responses of tropical Andean lakes to global change impacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 90 publications
2
10
0
Order By: Relevance
“…the most representative ones. These taxa are indicative of a wide range of environmental conditions, related to pH and nutrients (Benito et al 2020). This is consistent with the most frequent species reported in this study.…”
Section: Diatom Composition In the Context Of Mountain And Remote Lakessupporting
confidence: 91%
See 1 more Smart Citation
“…the most representative ones. These taxa are indicative of a wide range of environmental conditions, related to pH and nutrients (Benito et al 2020). This is consistent with the most frequent species reported in this study.…”
Section: Diatom Composition In the Context Of Mountain And Remote Lakessupporting
confidence: 91%
“…Diatoms are considered one of the algal groups with the largest number of species. In addition, they have specialized response to the environment (Benito et al 2020), which is quantitatively expressed through the ecological optimum and tolerances. The optimum is calculated as the weighted average of the abundance of a species with respect to a variable; the tolerance is calculated as the standard deviation.…”
Section: Aquatic Sciencesmentioning
confidence: 99%
“…Thus, we can conclude that the diatom communities in these lakes were generally resilient within their disturbance regimes—regardless of the nature and driver of that regime. Using a larger lake‐catchment database of modern and paleolimnological diatom samples, Benito et al (2020) showed that a combination of widespread climatic (i.e., Medieval Climate Anomaly) and local anthropogenic (historical human density) disturbances led to dynamically stable lake diatom assemblages by balancing increases and decreases of water conductivity and temperature seasonality. The existence of “good” modern analogues in the northern and central Andes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Across terrestrial, marine, and freshwater ecosystems, empirical studies highlight that spatial beta diversity can show distinct phases of stability (e.g. Benito et al ., 2020; Lindholm et al ., 2020 a , b ), punctuated by periods of biotic differentiation (e.g. Pinceloup et al ., 2020) or homogenisation (e.g.…”
Section: Synthesising Drivers and Directions Of Change In Spatial Bet...mentioning
confidence: 99%